Silica Nanoparticles Loaded With Selenium Quantum Dots Reduce Myocardial Ischemia-Reperfusion Injury by Alleviating Ferroptosis and Mitochondrial Dysfunction - Li T; Yang B; Liu X; Shi D; Wang Z; Chen Y; Shen C (International Journal of Nanomedicine)
Taixi Li,1,* Boshen Yang,1,* Xijian Liu,2 Dongmei Shi,1 Zhixiang Wang,1 Yizhi Chen,1 Chengxing Shen1 1Department of Cardiology, Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China; 2School of Chemistry and Chemical Engineering, Shanghai Frontiers Science Research Center for Druggability of Cardiovascular Noncoding RNA, Shanghai Engineering Technology Research Center for Pharmaceutical Intelligent Equipment, Shanghai University of Engineering Science, Shanghai, 201620, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chengxing Shen, Department of Cardiology, Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China, Email shencx@sjtu.edu.cnPurpose: Myocardial ischemia-reperfusion (IR) injury, a significant challenge in cardiovascular treatment, is primarily driven by ferroptosis and mitochondrial dysfunction. Despite extensive research, no clinical therapies effectively target ferroptosis in IR injury. This study aims to develop selenium-quantum-dot-loaded porous silica nanospheres (Se@PSN) as a novel therapeutic approach to address IR injury.Patients and Methods: Se@PSN were synthesized and tested for their reactive oxygen species (ROS) scavenging capabilities and biocompatibility. Additionally, the effects of Se@PSN on ferroptosis, mitochondrial damage, oxidative stress, and myocardial IR injury severity were evaluated.Results: Se@PSN enhanced the stability of selenium quantum dots and exhibited strong ROS scavenging abilities. Additionally, Se@PSN exhibited excellent biocompatibility. The Se@PSN treatment increased GPX4 levels, effectively inhibiting ferroptosis in cardiomyocytes. Furthermore, Se@PSN promoted the expression of mitochondrial respiratory complexes, mitigating oxidative phosphorylation damage and preserving mitochondrial function. These effects collectively resulted in reduced myocardial loss, inflammation, and fibrosis following IR injury. Compared to PSN alone, Se@PSN showed superior therapeutic efficacy against IR injury.Conclusion: Se@PSN exhibit great potential in reducing ferroptosis and protecting mitochondrial function, making them a promising therapeutic approach for the treatment of myocardial IR injury. Keywords: myocardial ischemia reperfusion, selenium, porous silica nanospheres, ferroptosis, reactive oxygen species